EVALUASI KINERJA GURU DALAM PEMBELAJARAN DI SDN KETAPANG 03 DENGAN MODEL CHARLOTTE DANIELSON - Nuvita Sari, Ela; Suhandi Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate teacher performance in learning at SDN Ketapang 03 using the Charlotte Danielson model. Employing a quantitative evaluative research approach, the study assesses four key aspects of teacher performance: planning and preparation, classroom management, instruction, and professional responsibilities. The results indicate that teachers achieved a performance score of 87% in planning and preparation, 89% in classroom management, 75% in instruction, and 73% in professional responsibilities. This research provides valuable insights for enhancing teacher effectiveness and overall education quality.